If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7s + -6 = 15 Reorder the terms: -6 + 7s = 15 Solving -6 + 7s = 15 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 7s = 15 + 6 Combine like terms: -6 + 6 = 0 0 + 7s = 15 + 6 7s = 15 + 6 Combine like terms: 15 + 6 = 21 7s = 21 Divide each side by '7'. s = 3 Simplifying s = 3
| -5x-107=9x+61 | | M/4.5=-7 | | x+4*9+6=15 | | -5.1x=510 | | 3x+5(6x-16)=85 | | 8x-9=8(x-3) | | 4*(x+2)=3(5-x) | | N+7=-4 | | -29-4x=-8x+59 | | S+1.3=-5.1 | | N+1*2=8 | | B+56.8=90.3 | | 3x^2+15x+1=0 | | -x-2/5=x+1/4+1/5 | | H+5.5=-23.5 | | 4x+5(3x+9)=110 | | 4r^2-35r-9=0 | | R-34=-11 | | 16/2 | | 6x-17=5x-17 | | 4x+x^2=11 | | -2x-7y=9 | | V-9.8=13.2 | | 8t^2+22t-21=0 | | M-9.9=.1 | | -97-7x=2x+101 | | 2-[3(x+4)+5x]=54 | | T+6.4=10.2 | | -2x+2y=18 | | 6p^2-p-35=0 | | 4(6ax+y)=23ax-3y | | (3y+2)(y+2)=0 |